Nonexistence results for some nonlinear elliptic and parabolic inequalities with functional parameters - Evgeny Galakhov; Olga Salieva; Liudmila Uvarova (Electronic Journal of Qualitative Theory of Differential Equations, 2015)
We obtain results on nonexistence of nontrivial nonnegative solutions for some elliptic and parabolic inequalities with functional parameters involving the $p(x)$-Laplacian operator. The proof is based on the test function method.